Assessment on public perception towards the development of 1Malaysia youth cities - Rabe, Noor Suzilawati; Mohamed Osman, Mariana; Abdullah, Muhammad Faris (American Scientific Publishers, 2017)
By 2025, Millennials who represent the youth generation born between 1980 to 1995 will represent more than 75% of global population. Youth are the future decision makers and key stakeholder of the society as well as the future leaders of the country. Therefore, it is imperative for current planning and development include youth participation in order to contribute to a sustainable future. This study assesses youth perception towards the development of 1Malaysia Youth Cities. Using questionnaire survey, the questions were designed to assess the respondents’ knowledge, awareness and perception on the development of Youth Cities. The analysis found that the provision of affordable housing was selected as the most important and ideal characteristics of Youth Cities, while self-empowerment and skill enhancement as the least ideal characteristics of Youth Cities. Moreover, result of Spearman test shows that there is a relationship between respondents socio-demographic background with their perception towards the ideal concept of Youth Cities in Malaysia.